A new species of Fillus Navás, 1919 (Neuroptera: Ascalaphidae) from the Brazilian Amazon Basin - Machado, Renato José Pires; Rafael, José Albertino (Zootaxa, 2011)
Fillus Navás, 1919 is a genus with two species: F. brethesi Navás, 1919 from Argentina and F. paradoxus (Weele, 1908) from Paraguay. Here we describe F. amazonicus n. sp., from Itapiranga, Amazonas, the first genus record for Brazil, extending its geographical distribution to the Amazon Basin.